A novel fluorescent probe for the early detection of prostate cancer based on endogenous zinc sensing. Issue 12 (26th July 2019) - Fu, Shibo; Wan, Xiang; Du, Chenchen; Wang, Hongyu; Zhou, Juan; Wang, Zhong
Abstract: Background: The early detection of prostate cancer can significantly optimize the prognosis, prolong patient lifespan, and improve quality of life. It has been well documented that prostate cancer tissues have lower zinc content than normal prostate tissues due to an impairment of the zinc accumulation mechanism. Methods: A novel diketopyrrolopyrrole (DPP)‐based fluorescent zinc ion probe named DPP‐C2 was prepared. The fluorescent intensity of this novel molecule is in direct proportion to environmental zinc concentration. Malignant (DU145 and PC3 cells) and normal prostate epithelial RWPE‐1 cells were tested. Prostate cancer tissues were also cultured and observed as tissue sections. The probe was also intravenously administered to tumor‐bearing (DU145 and PC3 cells) nude mice and observed under a whole‐body fluorescence live‐imaging system. Results: The probe showed minimal cytotoxicity to malignant and normal prostate cells. The RWPE‐1 cells showed not only stronger baseline fluorescence but also a significant increase in signal intensity after culturing in a zinc‐supplemented medium. In human prostate sections, the pathologically confirmed cancer tissues exhibited weaker fluorescence signals than normal and benign hyperplastic tissues. With proper excitation, prostate tissues revealed more intense fluorescence signals than tumor tissues, whereas other surrounding tissues showed almost no fluorescence. Conclusions: The novel zinc ion fluorescent probe DPP‐C2 is low toxic and showed potential application for the early detection of prostate cancer based on endogenous zinc sensing.